The Assessment of Professionalism for Ambulance Personnel – Problems and Challenges - Dambe, Gundega; Atstāja, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of this paper is to clarify whether annual knowledge testing at a work place promotes Ambulance professionals for personnel development, and if it providesthe possibility to assess personnel’s competence and professionalism. The results of 1693 ambulance personnel’s annual knowledge testing in years 2011, 2012,2013 are analysed in the research. The results obtainedreflect that in all stages knowledge improves, but there are not possibility to assess personnel’s competence and professionalism for building personnel development programs in the future.